Impact of music type on motor coordination task performance among introverted and extroverted students. Issue 3 (2nd July 2020) - Jamshidzad, Maryam; Maghsoudipour, Maryam; Zakerian, Seyed Abolfazl; Bakhshi, Enayatollah; Coh, Paul
Abstract : Purpose . People are interested in music. In this study, we assessed the impact of music type on objective performance. Materials and methods . We distributed 64 medical science students in Tehran into four groups: Iranian pop music, traditional music, Mozart's classical music and control groups. All participants performed the two-arm coordination test once without music and once with music (except for the control group), with an interval of 1 week. In the music groups, music was playing during the performance of the test. Participants were categorized as either introverted or extroverted and were distributed equally in the groups. Results . There was a significant decrease of test time in the second trial, observed in all music groups, and no significant difference identified in the control group. The traditional music group had less difference of mean time compared to the pop music group. The differences in the traditional and classical groups were not significantly different. In the music groups, both extroverted and introverted students decreased their test time significantly after music intervention, but extroverted students decreased more. Conclusion . Listening to music would enhance the speed of performance. Music with a higher tempo, such as pop music, increased the speed more.